The Art of Spatial Illusion: Immersive Encounters Between People, Media, and Place - Koeck, Richard 1969- (London New York Routledge Taylor & Francis Group, 2025)
"Contemporary art, entertainment and architecture cultures offer a growing amount of digitally mediated spatial experiences, situated either in the metaverse (e.g VR) or location-based in physical realms (e.g. AR), increasingly powered by generative systems (e.g. AI). Are such spatially "immersive experiences" a new phenomenon and dependent on digital innovation? The Art of Spatial Illusion: Immersive Encounters between People, Media, and Place is an insightful exploration of the evolving relationship between humans, media, and spatial environments, tracing their progression from the Renaissance, via Modernity and Postmodernity to today's digital age. The author offers a compelling reading and re-evaluation of architectural history and media theory, drawing connections between historical practices, technological innovations and contemporary immersive experiences. Inspired by scholars such as Walter Benjamin and Jean Baudrillard, the book discusses how technological advancements have transformed our situatedness in "image-spaces", highlighting the shift from material authenticity to digital reproductions. The book is structured into four parts - THE SURFACE, THE STAGE, THE INTERFACE, and THE HYBRID - each exploring different aspects of spatial illusions and their implications. It offers a critical perspective on the creation of architectural, immersive environments, examining the motivations behind them and their broader cultural and political contexts. Richly illustrated and deeply researched, The Art of Spatial Illusion is an essential reading for anyone interested in architecture and art as well as media archaeology, history, and theory. Seeing new, thought-provoking architectural propositions emerging on our horizon, the author provides a comprehensive understanding of how immersive experiences shape our perception of reality"--
Keywords: Philosophy; Architecture